Molecular systematics of the genus Hypnea (Rhodophyta) in South Africa, with the description of a new genus, Tenebris (Cystocloniaceae, Rhodophyta) - Johnson, Victoria Jane (Department of Biological Sciences, 2018)
Hypnea, an economically important genus of red algae (containing κ-carrageenan) found globally on tropical and subtropical shores, is shrouded in taxonomic confusion due to morphological plasticity of species and general lack of clear morphological characters. Of 113 species described worldwide only half of that number is accepted taxonomically. Of the 11-recorded species in South Africa there are currently 8 recognised (Hypnea arenaria, H. ecklonii, H. intricata, H. musciformis, H. rosea, H. spicifera, H. tenuis and H. viridis). Some of these species are difficult to tell apart and appear to differ only in dimensions, which overlap in some species. In addition, some entities do not fit the descriptions currently in existence for these species and some have not been recorded since description. This study aimed to use morphological and molecular techniques to re-examine as many South African Hypnea entities as possible, in order to improve the taxonomic understanding of this group. Collections were done along the coast of South Africa, Mozambique, Madagascar and Europa Island. Samples were pressed as herbarium specimens, preserved in 5% formalin in sea water for morphological and anatomical analysis, and dried in silica gel for sequencing. DNA was extracted from dried samples and mitochondrial (cox1) and plastid (rbcL) DNA sequences were obtained. Sequences were assembled, aligned by eye, and analysed using maximum likelihood, Bayesian analyses, and genetic distance (GD) matrices for molecular analysis. Specimens were sectioned and photographed for morphological analysis. The results uncovered different organisation of the Hypnea genus than previously recorded. Specimens which fitted the description of Hypnea rosea were found to form a complex containing two molecularly distinct morphotypes (1,7% GD in rbcL; 6,8% GD cox1) with a link to H. cervicornis. Hypnea viridis is shown to be closely linked to the tropical Hypnea pannosa (1,7% GD in rbcL), Hypnea spicifera, although very morphologically variable, was found to comprise one species. There is a clade which could represent Hypnea cf. intricata - a species with a very brief type description that matches with the morphology of these specimens. Hypnea musciformis does not exist here, because none of the specimens that fitted the South African description were even closely linked to H. musciformis from close to the type locality (Trieste, Italy). They came out in the H. rosea clades and the H. cf. intricata clade. Hypnea ecklonii could not be recognised among any of the specimens that were studied. There are two new records of Hypnea cf. pannosa and Hypnea cf. cervicornis for South Africa. All of the specimens that fitted the descriptions of H. tenuis were molecularly unrelated to any of the Hypnea species for which DNA sequences were available (rbcL GD >11%). However, they fit in the Cystocloniaceae with their closest relatives being Calliblepharis ciliata, Hypnea viridis and Hypnea pannosa (rbcL GD >8%). These GD values are large enough that these two species form a separate genus. Therefore, I describe a new genus of Cystocloniaceae, Tenebris V. Johnson, J. Bolton, L. Mattio, R. Anderson gen. nov. This appears morphologically very similar to Hypnea, but differs molecularly. The morphological differences include size ratio of central filament to periaxial cells - where present, Hypnea central cells are significantly smaller than pericentral cells while Tenebris pericentral cells are similar in size to the central filament. Tenebris spp. are also much smaller than the Hypnea spp. Hypnea tenuis Kylin is re-assigned to Tenebris tenuis (Kylin) V Johnson, JJ Bolton, L Mattio, RJ Anderson comb. nov. The second species is based on only one specimen, and although it is somewhat similar to the type description of Hypnea arenaria, without more evidence, it is provisionally named Tenebris sp. In total, there are 13 molecular clades of South African sequences in this study: 7 Hypnea clades identified to species level, 2 unidentified Hypnea which cluster with no other Hypnea species, 2 unidentified and distinct sequences which are not Hypnea, and 2 species assigned to a new genus Tenebris. In conclusion, the 7 South African Hypnea are: Hypnea cf. cerviconis, H. cf. intricata, H. cf. pannosa, H. rosea sp. 1, H. rosea sp. 2, H. spicifera, and H. viridis. The unidentified Hypnea spp. are in clades G and I. The unidentified sequences from a different genus are in clade H. There are 2 species Tenebris tenuis and Tenebris sp. assigned to the new genus.